2013
DOI: 10.7763/ijbbb.2013.v3.298
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Heart Valve Disorders through Trapezoidal Features and Hybrid Classifier

Abstract: Abstract-Numerous studies are being conducted in recent years focusing on phonocardiographic (PCG) signals due to their capability to characterize heart sounds. These characteristics can be exploited in developing computer-aided auscultation system as a complementary tool for clinicians in diagnosis of cardiovascular disorders. This study proposes a new type of features to distinguish five categories of heart sounds, including normal, mitral stenosis, mitral regurgitation, aortic stenosis, and aortic regurgita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In the literature, both supervised (Das et al, 2019; Moulana et al, 2022) and unsupervised (Das et al, 2020; Torre‐Cruz et al, 2022) approaches of heart health status detection have been reported. The unsupervised methods, despite their potential, have some limitations about their usability and accuracy (Safara et al, 2012). Since a labelled dataset is at hand (PhysioNet 2016), the proposed work focuses on a supervised method of depicting cardiac health status.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, both supervised (Das et al, 2019; Moulana et al, 2022) and unsupervised (Das et al, 2020; Torre‐Cruz et al, 2022) approaches of heart health status detection have been reported. The unsupervised methods, despite their potential, have some limitations about their usability and accuracy (Safara et al, 2012). Since a labelled dataset is at hand (PhysioNet 2016), the proposed work focuses on a supervised method of depicting cardiac health status.…”
Section: Introductionmentioning
confidence: 99%
“…Systems are devised in (Ahmad, 2011;Grzegorczyk et al, 2016;Hofmann et al, 2016) to interpret the condition of heart valves as normal or abnormal without further classifying the abnormal ones, while in (Emre & Uguz, 2011;Uğuz, 2012), the valvular heart condition is interpreted as one of the three cases (normal, mitral stenosis, pulmonary stenosis). Furthermore (Noman et al, 2018) presents a novel system to diagnose four valvular heart cases (normal, aortic regurgitation, mitral stenosis, mitral regurgitation), whereas in (Safara et al, 2013;Suboh et al, 2008;Suhas et al, 2017), five valvular heart cases (normal, aortic stenosis, aortic regurgitation, mitral stenosis, mitral regurgitation) are diagnosed. In (Kumar et al, 2018), a system is devised to diagnose five heart valve diseases (aortic stenosis, aortic regurgitation, mitral stenosis, mitral regurgitation, pulmonary stenosis).…”
Section: Introductionmentioning
confidence: 99%
“…These are called murmurs. They are generally high-frequency, noise like sounds that are produced as a result of turbulent blood flow [2]. Intensity, frequency content, split information, time relations, location of murmurs etc.…”
Section: Introductionmentioning
confidence: 99%